2018
DOI: 10.1136/bcr-2017-222843
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tibiofibular joint dislocation treated using flexible and permanent syndesmosis fixation

Abstract: We present the case of a 40-year-old man who suffered an isolated proximal tibiofibular dislocation of the left knee after a trauma during a soccer game. Physical examination and radiographic imaging revealed an anterolateral dislocation of the proximal fibula. The diagnosis was confirmed by MRI. The treatment choice was open reduction and internal fixation under direct visualisation using flexible and permanent internal fixation. Postoperative treatment includes knee immobilisation during the first week, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 12 publications
(8 reference statements)
0
24
0
Order By: Relevance
“…Due to heterogeneity and scant evidence, there is currently no consensus on the definitive study and management of DPTJ [7]. As described in this case, most authors agree that clinical suspicion must be thorough and be confirmed with images, starting with radiography, and complementing with CT if suspicion persists [8,9]. However, magnetic resonance can also be helpful in differential diagnosis or in chronic cases [7].…”
Section: Discussionmentioning
confidence: 99%
“…Due to heterogeneity and scant evidence, there is currently no consensus on the definitive study and management of DPTJ [7]. As described in this case, most authors agree that clinical suspicion must be thorough and be confirmed with images, starting with radiography, and complementing with CT if suspicion persists [8,9]. However, magnetic resonance can also be helpful in differential diagnosis or in chronic cases [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, flexible suture fixation could be considered for the PTFJ and/or syndesmosis. Flexible fixation for either isolated PTFJ injuries or combined PTFJ with syndesmosis injuries has been described 8,9 . Although Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the most common fracture morphology associated with proximal tibiofibular injury was a tibial shaft fracture (Figure 2 ) (68.75%), which is consistent with previous studies. 10 , 21 Of the many case reports published on this topic, 9 10 11 12 13 14 15 16 17 18 19 20 21 this systematic review was only able to identify three larger case series that have published the epidemiology of these injuries. Herzog et al 2 published a similarly high rate of open fracture (76.7%) and peroneal nerve palsy (36%) with their series of 30 proximal tibiofibular injuries; however, their rate of vascular injury was lower at 6.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 5 6 7 8 There is overall a paucity of literature on traumatic dislocations of the proximal tibiofibular joint, although a few small case studies have been reported. 9 10 11 12 13 14 15 16 17 18 19 20 21 There is similarly no systematic review of the literature on this topic.…”
mentioning
confidence: 99%